Pencegahan Demam Berdarah Dengue (DBD) Melalui Gerakan 3M Plus di Posyandu Puskesmas Tanjung Karang - Wasliah, Indah; Syamdarniati (Jurnal Ilmiah Pengabdian dan Inovasi, 2025)
Dengue Hemorrhagic Fever (DHF) remains an endemic disease and a significant public health issue in Indonesia, including in the service area of Tanjung Karang Public Health Center. Prevention efforts can be implemented through community empowerment using the 3M Plus method: draining water containers, covering water storage, burying used items, and additional measures such as using larvicides and mosquito nets. This community service activity aimed to raise awareness and encourage active participation of residents in DHF prevention through education and hands-on practice of the 3M Plus strategy at the local Posyandu (integrated health post). The methods used included health education sessions, live demonstrations, and distribution of educational materials to participants. The results indicated an increase in public knowledge about the dangers of DHF and the importance of maintaining environmental hygiene. The program also successfully encouraged community members to regularly implement 3M Plus measures in their households. With a participatory and community-based approach, this program proved effective as a promotive and preventive effort in DHF control.